Projection Effects and the Role of Political Ambiguity. (30th December 2020) - Martin, Danielle; Banducci, Susan; Stevens, Daniel; Coan, Travis
Abstract: Scholars studying political perceptions find evidence of the presence of projection effects. Yet several questions still need to be explored as to the time frame of the effect and the factors affecting projection. In particular, although the effect of ambiguity on projection has often been assumed and has been tested in a formal model (Jensen, 2009), no empirical evidence supports the idea that ambiguity fosters projection. We analyze an online survey conducted before and after the 2017 UK General Election. In addition to testing for the presence of projection effects on four different policy issues, we show that ambiguity fosters projection. This result suggests that ambiguity is not always necessarily a good strategy for political parties.